Bruce Reidel, What We Won: America’s Secret War in Afghanistan 1979-89 - Mr. Majid Mahmood (CISS Insight Journal, 2015)
The book titled “What We Won, America’s Secret War in Afghanistan 1979-89” written by Bruce Reidel is a detailed study of actors involved, conduct and lessons learnt from one of the biggest US covert operations in its history during the Afghanistan war of the 1980’s. The book also addresses the reasons of success of covert operations and intelligence struggle against the Soviet 40th Red Army in Afghanistan and the role played by key decision makers in Carter and Reagan administrations in the United States and General Zia’s regime in Pakistan. The book draws some lessons from that war which can be further studied and explored to understand the dynamics of insurgencies and counter insurgencies. The book contains nine chapters divided in two parts. The first part explores the major players and combatants in the Afghan conflict such as Afghan Communists, the Soviets, Afghan Mujahideen, Pakistan’s then President General Zia ul Haq, and Saudi Arabia. Five chapters are dedicated in this section to evaluate the part played by each of these five players who played a significant role during the Afghan conflict.